Role of Peer and Self-Assessment Practices for Enhancing Critical Writing in EFL High School - Tarigan, Fatin Nadifa; Zahiri, Arsi; Heridayani, Heridayani; Siregar, Nurmaliana Sari (Journal of English Education and Teaching, 2025)
This study examines the effect of peer and self – assessment practices on high school students’ critical writing in English as a Foreign Language (EFL) context. A quasi-experimental design with two groups was employed with the intervention lasting six weeks. The participants were 60 students of the eleventh grade from a private high school in Medan. Peer and self-assessment using analytic rubrics were implemented in the experimental group, while the conventional teacher feedback was applied in the control group. The students’ writing performance was measured through pretest and posttest. In addition, qualitative data were collected using open-ended questionnaires to explore the students’ perception in implementing peer and self-assessment. The findings revealed a significant improvement in the experimental group especially in the aspect of argument development and critical reflection, compared to the control group. The findings also indicated the students’ awareness of writing and confidence increase after the implementation of peer and self-assessment in the experimental group. Overall, peer and self-assessment encouraged active engangement in the writing process and supported the development of critical thinking skills. It can be concluded that peer and self-assessment are effective in enhancing critical writing among high school EFL students.